Gold(I)-catalyzed intramolecular cyclization/intermolecular cycloaddition cascade as a fast track to polycarbocycles and mechanistic insights - Zhang, Cheng; Hong, Kemiao; Pei, Chao; Zhou, Su; Hu, Wenhao; Hashmi, A. Stephen K.; Xu, Xinfang (Nature Communications, 2021)
Metal carbene is an active synthetic intermediate, which has shown versatile applications in synthetic chemistry. Although a variety of catalytic methods have been disclosed for the generation of carbene species from different precursors, there is an increasing demand for the development of efficient and practical approaches for the in-situ formation of metal carbene intermediates with structural diversity and unrevealed reactivity. Herein we report a gold-catalyzed cascade protocol for the assembly of polycarbocyclic frameworks in high yields under mild reaction conditions. Mechanistic studies indicate that the unique β-aryl gold-carbene species, generated via gold-promoted 6-endo-dig diazo-yne cyclization, is the key intermediate in this reaction, followed by a [4 + 2]-cycloaddition with external alkenes. In comparison to the well-documented metal carbene cycloadditions, this carbene intermediate serves as a 4-C synthon in a cycloaddition reaction. A variety of elusive π-conjugated polycyclic hydrocarbons (CPHs) with multiple substituents are readily accessible from the initially generated products by a mild oxidation procedure.